Density and biomass of aphid communities (Homoptera, Aphididae)in winter wheat crop and sugar beet crop in the vicinity of Turew (Poznań region, Poland) - Krzywiec, Danuta (Polish Scientific Publishers, 1988)
The paper presents results of two years of investigations on aphid communities in winter wheat crop and aftercrop and in sugar beet crop (species composition, numbers, density, biomass and morph-age structure of the populations of dominant species Sitobion avenae (F.) and Aphis fabae Scop.). In 1979, there was an outbreak of S. avenae. The average density of the community was: 1648 indiv. · m-2, biomass 237.8 mg d. wt. · m-2. But in 1980 density and biomass of A.fabae were exceptionally low; mean density of the community was 36.1 indiv. · m-2 and biomass was 3.7 mg d. wt. · m-2.
Pages 531-543 : illustrations ; 24 cm
Bibliographical references (pages 542-543)
Abstract in Polish
Keywords: aphids; species composition; density; biomass; morph-age structure; cultivated fields